EXPLORING CULTURAL AND INTERCULTURAL DIMENSIONS IN ENGLISH LANGUAGE TEACHING: A SYSTEMATIC REVIEW OF TEACHER AND LEARNER PERSPECTIVES - Nurmaisyah, Nurmaisyah (Universitas Muhammadiyah Lampung, 2025)
The integration of culture and intercultural communicative competence (ICC) into English language teaching (ELT) has become an essential focus in language education, particularly within English as a Foreign Language (EFL) contexts. This systematic review synthesizes findings from 23 empirical studies conducted across diverse geographical and educational settings. The review research question is (1) How do English language teachers perceive and implement ICC in EFL/ESL classrooms across different cultural contexts. The analysis reveals that teachers’ perceptions of ICC are generally positive, but actual classroom practices often depend on contextual factors such as institutional support, training, and cultural familiarity. A significant gap remains between theoretical recognition of ICC and its practical application. Key challenges include insufficient pedagogical guidance, limited resources, and lack of assessment strategies. Conversely, studies highlight opportunities in using culturally relevant materials, narrative texts, and experiential learning to foster intercultural understanding. The review further finds that embedding cultural content in ELT can enhance learner motivation, promote autonomy, and improve intercultural sensitivity. This review underscores the importance of equipping educators with the skills and frameworks necessary to teach culture effectively. It also calls for future research focused on longitudinal impacts, student perspectives, and the development of context-sensitive ICC pedagogies. Keywords: intercultural communicative competence, cultural awareness, English language teaching, intercultural sensitivity, systematic review.